Extraction and Characterization of Hemicellulose from Eucalyptus By-product: Assessment of Enzymatic Hydrolysis to Produce Xylooligosaccharides - Mafei, Thamyres Del Torto [UNESP]; Neto, Flávia Sanchez Penalva Pinto [UNESP]; Peixoto, Guilherme [UNESP]; de Baptista Neto, Álvaro [UNESP]; Monti, Rubens [UNESP]; Masarin, Fernando [UNESP] (Springer Nature, 2019)
Eucalyptus wood is the primary source of fibers to produce paper and cellulose in South American countries. The major by-product generated in the cellulose industry is sawdust derived from chip wood production, which is designated as Eucalyptus by-product (EB). The xylooligosaccharides (XOS) are xylose-based oligomers with proven effects over maintenance and stimulation of beneficial human gut bacteria. This study reported the EB extraction and characterization along with an assessment of hemicellulose hydrolysis using commercial xylanases to produce XOS. Hemicellulose derived from extracted and NaClO2 pretreated (HEEBPT) presented xylan content of 55%, which was similar to 58.5% found in commercial Birchwood hemicellulose (CBH). The enzymatic hydrolysis of HEEBPT and CBH presented 30% as maximum conversion of xylan into XOS without significant difference among the enzymatic extracts evaluated. The XOS production from EB was proven as a technically feasible alternative to recover a value-added product from hemicellulosic fraction generated in the cellulose industry. However, lignin removal with NaClO2 from EB affects the feasibility of an industrial process because they generate toxic compounds in the pretreatment step. Thus, further studies with alternative reagents, such as ionic liquids, are required to asses selectively lignin removal from EB. [Figure not available: see fulltext.].
Keywords: Chemical composition; Enzymatic hydrolysis; Eucalyptus by-product; Hemicellulose extraction; Xylooligosaccharides